2023
DOI: 10.1021/acs.iecr.3c03132
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of Np(IV) and Pu(IV) with Hexa-n-octyl nitrilotriacetamide (HONTA) in an Ionic Liquid: Unusual Species vis-à-vis a Molecular Diluent

Rajesh B. Gujar,
Bholanath Mahanty,
Seraj A. Ansari
et al.

Abstract: The extraction of Np(IV) and Pu(IV) was studied using a tripodal amide ligand (N,N,N′,N′,N″,N″-hexa-n-octyl nitrilotriacetamide termed as HONTA) in an ionic liquid (C 4 mim• NTf 2 ) as well as in a molecular diluent mixture (95% n-dodecane +5% iso-decanol) from an aqueous feed containing diluted nitric acid. The extraction efficiency of Pu(IV) was higher than that of Np(IV), while the RTIL-based solvent system extracted the metal ions better than the molecular diluent-based solvent system. The extracted specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Similarly, tripodal ligands with three carbamoyl methylene phosphine oxide (CMPO) moieties have shown highly efficient complexation with trivalent lanthanide/actinide ions. On the other hand, tripodal amide ligands where three amide moieties are tethered to a central N -atom have shown great promise in the extraction of trivalent lanthanides as well as actinide ions. , Subsequently, Sasaki et al , reported separation of trivalent lanthanides and actinides with preferential extraction of Am 3+ ions where the actinide ion was suggested to bind to the pivotal N -atom by a “soft–soft” interaction, resulting in a separation factor ( D Am / D Eu ) value in the excess of 50. The extraction of a hexavalent actinide ion such as UO 2 2+ and tetravalent actinide ions, viz., Pu 4+ and Np 4+ , has been studied by our research group in the last 2 years. Furthermore, the role of the spacer length between the tripodal N -atom and the amidic carbon has been investigated with interesting results …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, tripodal ligands with three carbamoyl methylene phosphine oxide (CMPO) moieties have shown highly efficient complexation with trivalent lanthanide/actinide ions. On the other hand, tripodal amide ligands where three amide moieties are tethered to a central N -atom have shown great promise in the extraction of trivalent lanthanides as well as actinide ions. , Subsequently, Sasaki et al , reported separation of trivalent lanthanides and actinides with preferential extraction of Am 3+ ions where the actinide ion was suggested to bind to the pivotal N -atom by a “soft–soft” interaction, resulting in a separation factor ( D Am / D Eu ) value in the excess of 50. The extraction of a hexavalent actinide ion such as UO 2 2+ and tetravalent actinide ions, viz., Pu 4+ and Np 4+ , has been studied by our research group in the last 2 years. Furthermore, the role of the spacer length between the tripodal N -atom and the amidic carbon has been investigated with interesting results …”
Section: Introductionmentioning
confidence: 99%
“…The main focus of the NTAamides, as discussed earlier, is the complexation and separation of trivalent actinides with less or no emphasis on understanding its complexation. For example, the extraction of Th 4+ , Pu 4+ , Np 4+ , and UO 2 2+ ions with NTAamides has been reported extensively, but the fundamental aspects of the complexation are missing at large. One may assume that the complexation of NTAamides with smaller actinide cations like Th 4+ , Pu 4+ , and Np 4+ may be similar to those observed with lanthanides where the central N atom of the ligand is also coordinating; it may not be true with those of large actinyl cations like UO 2 2+ ions. Here, one may expect that due to the presence of two axial O atoms in uranyl cation, the central N atom of NTAamide may not be in the position to coordinate with the central metal.…”
Section: Introductionmentioning
confidence: 99%